2014
DOI: 10.1021/am501724h
|View full text |Cite
|
Sign up to set email alerts
|

WO3 Nanoparticle-Based Conformable pH Sensor

Abstract: pH is a vital physiological parameter that can be used for disease diagnosis and treatment as well as in monitoring other biological processes. Metal/metal oxide based pH sensors have several advantages regarding their reliability, miniaturization, and cost-effectiveness, which are critical characteristics for in vivo applications. In this work, WO3 nanoparticles were electrodeposited on flexible substrates over metal electrodes with a sensing area of 1 mm(2). These sensors show a sensitivity of -56.7 ± 1.3 mV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 41 publications
7
96
0
Order By: Relevance
“…Recently, a tungsten oxide conformable sensor based on coatings from WO 3 nanoparticles electrodeposited on flexible substrates was developed. The authors showed the possibility to achieve in such configuration a near‐Nernstian response of −56.7 ± 1.3 mV pH −1 a pH range of 5–9 …”
Section: Applicationsmentioning
confidence: 99%
“…Recently, a tungsten oxide conformable sensor based on coatings from WO 3 nanoparticles electrodeposited on flexible substrates was developed. The authors showed the possibility to achieve in such configuration a near‐Nernstian response of −56.7 ± 1.3 mV pH −1 a pH range of 5–9 …”
Section: Applicationsmentioning
confidence: 99%
“…[ 21 ] On the other hand, inorganic semiconductors processed under optimized conditions (i.e., with proper deposition parameters and stoichiometry) can be quite stable over time, even without any encapsulation layer. Examples range from wearable biomedical devices [ 5 ] to active matrix backplanes of bendable and transparent organic light emission device (OLED) displays. [ 24,25 ] Nonetheless, it also fi nds applications in other fi elds of electronics and electrochemistry such as gas sensing in single electron transistors, [ 26 ] sensitive layer in ion-sensitive fi eld-effect transistors (ISFETs), [ 27 ] or even as high-κ dielectric in transparent FETs.…”
Section: Doi: 101002/aelm201500030mentioning
confidence: 99%
“…[24][25][26][27][28][29][30] Concretely speaking, the pH sensing mechanism relies on the establishment of a surface equilibrium between the metal (M) and its oxide (MOx) when in contact with the test medium:…”
Section: Resultsmentioning
confidence: 99%